Financial Stability, Personal Financial Need, Financial Target, External Pressure dan Financial Statement Fraud - Purnama, Sukma Indah; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2022)
The purpose of this study was to empirically examine the influence of pressure factors consisting of financial stability, personal financial need, financial target and external pressure on financial statement fraud. The research sample was 147 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The data was obtained from secondary data from the annual report of manufacturing companies (2015-2019) which was then analyzed by multiple linear regression. The results showed that there was an effect of financial stability and financial target variables on financial statement fraud, but on the contrary, there was no influence between personal financial need and external pressure variables on financial statement fraud. Keywords :  Financial Stability; Personal Financial Need; Financial Target; External Pressure; Financial Statement Fraud.